Mind the Gap: A Collaborative Competence E-learning Model Evolving Between University and Industry - Hattinger, Monika; Eriksson, Kristina (Journal of Strategic Innovation and Sustainability, 2020)
This article arises from consideration of the effects of inter-organizational collaboration on participating partners, specifically from design-related activities and co-production of e-learning courses. The research focus is on critical factors for inter-organizational collaborative e-learning and co-production between university and industry. We describe the process of a six-year longitudinal collaborative action research project comprising six cases and three phases—initialization, implementation, and dissemination. The analysis is conducted from a multi-stakeholder perspective: managers, teachers, and practitioners. The overall aim is development of a sustainable collaborative competence e-learning model that will increase industrial employees’ competencies. This work’s main contribution is the finding that co-production of knowledge entails three levels of activities among actors: insight into the purposes and practices of others, capacity to transform the problems of a practice and build common knowledge together, and finally, the capacity to mutually co-produce knowledge acted upon for transformation in the workplace.